The effect of peer education on management of chemotherapy side effects in patients with cancer - Leyla Alilu; Leila Heydarzadeh; Hossein Habibzadeh; Javad Rasouli (Wolters Kluwer Medknow Publications, 2021)
Background: Chemotherapy drugs may have numerous side effects for patients. Thus, this study was conducted with the aim to determine the effect of peer education on the management of chemotherapy side effects in patients with cancer. Materials and Methods: This randomized, controlled trial was conducted on 80 patients with cancer in 2018. They were allocated to two groups of intervention and control. The self-care education on chemotherapy side effects was provided by the peers to the individuals in the intervention group. The data collection tools included a demographic characteristics form and the Self-Care Diary (SCD). Data analysis was performed using independent t-test and Chi-square test in SPSS software. Results: The results showed that the mean scores of the effectiveness of self-care behaviors were significantly higher in the intervention group compared to the control group after the intervention (p < 0.05). Conclusions: Peer education is recommended for cancer patients undergoing chemotherapy.